Recognition of Telecommunication Networks States - Jankūnienė, R.; Gudonavičius, R. (Elektronika ir Elektrotechnika, 2000)
The one of basic TMN network functions can be the foreseeing of critical states of telecommunications network operability according measured network’s quality parameters. For that purpose the estimation process of network operability states can be divided into two stages: the estimation of standards for network states and classification of network situations by using classification algorithms. This article presents the recognition of telecommunications networks states mathematical model by using Bayesian classificator and specific modeling results, that present us the probability of network operability state ("good", "satisfactory" and "bad").